Edukasi Asupan Zat Besi dalam Meningkatkan Kadar Hemogobin (Hb) pada Remaja Putri Sebagai Upaya Dini Pencegahan Stunting - Indah Wasliah; Syamdarniati (LPPM STIKES Mataram, 2024)
Introduction: Indonesia is still facing nutritional problems which have a serious impact on the Quality of Human Resources. One of the nutritional problems that has become the main concern at this time is the high stunting of children under five. The prevalence of stunting that occurs in Indonesia in 2020 puts Indonesia to have a higher prevalence of stunting than other countries in Southeast Asia. Indonesia is in second place with the highest prevalence of stunting, reaching 31.8%. Efforts to break the chain of stunting problems need to be strengthened in the youth group by providing iron education to prevent stunting. Objective: To determine the effect of education on iron intake on increasing Hb in female adolescents as an early effort to prevent stunting. Design: Quasi experimental design with one group pretest and posttest. The number of samples in this study were 29 people who were taken by total sampling technique. Results: The t-test analysis showed that there was an effect of education on iron intake on increasing Hb with a p value of 0.034. Conclusion: Thus, education on iron intake can be applied as an early effort to prevent stunting.